DETECTION OF BIO-ENERGY CHANGE AFTER 1-HR YOGA BY USING AURA-COM - Supalaknaree, Suree (Interprofessional Journal of Health Sciences, 2023)
Bio-energy (Chi, Prana and others) is essential for life as it helps providing essential energy to maintain body functions. Bio-energy is generated and transferred internally by subtle energy centers (Chakra) and meridians channels to provide essential energy to nearby organs and systems. There are 7 main Chakras located along a spinal cord and thousands meridian channels connected between organs. Beside this, living organisms can gather bio-energy from external sources such as solar energy, natural energy (forest, river, mountain, sea, sand) and gem stones. Bio-energy is an electromagnetic field-generated energy or known as “Aura, protective shields for protecting physical body from bad energy. Yoga, a well-known oriental exercise, improves balance of body and mind. Therefore, monitoring of bio-energy markers can be used for prognosis of pathologic conditions. Aura-Com model AR 2000 was used for aura check in 16 volunteers (1Male and15 female, aged 19-27 years exchanged international students from Netherlands). Aura and bio-energy markers were monitored in all volunteers by placing both palms on hand-shaped bases of Aura-Com as autonomic nerves are most densely packed in the hands and it is convenient to obtain information of the body and the soul. In this study, micro-current from both palms of all volunteers were monitored tripicately before and after 1-hr Yoga by using Aura-Com AR 2000 for 4 times, once a week and 7 days apart. There were three aura pictures and three of each bio-energy markers i.e. vigor (activity), stability (relaxation), balance (of five elements) and energy level were recorded during each aura check . Total measurement 163 of all markers from 16 volunteers were used for statistically analysis using Paired T-test at P < 0.05 to determine whether or not bio-energy change after 1 hr-Yoga. The results showed statistically increased after 1 hr-Yoga at P < 0.05 of vigor, balance of five elements and energy level as following : vigor(activity), increased from 74.12 ± 13.44 to 77.47 ± 15.40; balance (of five elements), increased from 126.26 ± 20.68 to 131.43 ± 23.95; and energy level increased from 633.66 ± 105.63 to 660.43 ± 121.94. On the other hand, stability (relaxation) was statistically significant decreased at P < 0.05 after 1-hr Yoga from 23.15± 12.27 to 20.26± 13.95. In conclusion, yoga has high potential in rejuvenation of organs and system functions as indicated by increased bio-energy markers after 1 hr-Yoga. Therefore, regular yoga practice is recommended for better health conditions in both healthy persons and also in patients with some chronic diseases caused by aging or some chronic diseases e.g. headache, office syndrome mainly caused by blockage of bio-energy flow in the body.